Cost-effectiveness analysis of alternative colorectal cancer screening strategies in high-risk individuals. (April 2021) - Benamouzig, Robert; Barré, Stéphanie; Saurin, Jean-Christophe; Leleu, Henri; Vimont, Alexandre; Taleb, Sabrine; De Bels, Frédéric
Background and aims: Current guidelines recommend colonoscopy every 3–5 years for colorectal cancer (CRC) screening of individuals with a familial history of CRC. The objective of this study was to compare the cost effectiveness of screening alternatives in this population. Methods: Eight screening strategies were compared with no screening: fecal immunochemical test (FIT), Stool DNA and blood-based screening every 2 years, colonoscopy, computed tomography colonography, colon capsules, and sigmoidoscopy every 5 years, and colonoscopy at 45 years followed, if negative, by FIT every 2 years. Screening test and procedures performance were obtained from the literature. A microsimulation model reproducing the natural history of CRC was used to estimate the cost (€2018) and effectiveness [quality-adjusted life-years (QALYs)] of each strategy. A lifetime horizon was used. Costs and effectiveness were discounted at 3.5% annually. Results: Compared with no screening, colonoscopy and sigmoidoscopy at a 30% uptake were the most effective strategy (46.3 and 43.9 QALY/1000). FIT at a 30 µg/g threshold with 30% uptake was only half as effective (25.7 QALY). Colonoscopy was associated with a cost of €484, 000 per 1000 individuals whereas sigmoidoscopy and FIT were associated with much lower costs (€123, 610 and €66, 860). Incremental cost-effectiveness rate for FIT and sigmoidoscopy were €2600/QALY ( versus no screening) and €3100/QALY ( versus FIT), respectively, whereas it was €150, 000/QALY for colonoscopy ( versus sigmoidoscopy). With a lower threshold (10 µg/g) and a higher uptake of 45%, FIT was more effective and less costly than colonoscopy at a 30% uptake and was associated with an incremental cost–effectiveness ratio (ICER) of €4240/QALY versus no screening. Conclusion: At 30% uptake, current screening is the most effective screening strategy for high-risk individuals but is associated with a high ICER. Sigmoidoscopy and FIT at lower thresholds (10 µg/g) and a higher uptake should be given consideration as cost-effective alternatives. Plain Language Summary: Cost-effectiveness analysis of colorectal cancer screening strategies in high-risk individuals Fecal occult blood testing with an immunochemical test (FIT) is generally considered as the most cost-effective alternative in colorectal cancer screening programs for average risk individuals without family history. Current screening guidelines for high-risk individuals with familial history recommend colonoscopy every 3–5 years. Colonoscopy every 3–5 years for individuals with familial history is the most effective strategy but is associated with a high incremental cost–effectiveness ratio. Compared with colonoscopy, if screening based on FIT is associated with a higher participation rate, it can achieve a similar effectiveness at a lower cost.